The influence of personality and desires on motivation for selecting tourist destinations - Salazar Duque, Diego; Osorio Espín, María Alejandra (Mercados y Negocios, 2024)
The present study aims to analyze the relationship between a tourist’s personality traits and the diverse motivational factors that guide their selection of a travel destination. To conduct this research, we adopted a quantitative, cross-sectional approach, collecting information through a survey involving 384 participants in Quito. The results revealed that potential tourists consider various factors, including their needs, desires, available offerings, and personality traits, when choosing a destination. However, it was established that personality traits do not significantly influence tourism needs and offerings. Furthermore, desires do not serve as direct or indirect mediating variables between needs and offerings. In conclusion, an individual’s personality does not necessarily dictate motivation when selecting a tourist destination. This study provides a comprehensive view of how psychological and motivational factors interact in the complex decision-making process within tourism.